Iowa Ornithologists' Union, Quarterly field report, fall 1994 - Kent, Thomas H. (Thomas Hugh), 1934-et al; Iowa Ornithologists' Unionet al (1994)
Thomas Kent notes that the fall season was outstanding for rarities, that the Records Committee will clarify which birds need documentation, and that a new field checklist will be published in 1995. Quarterly field report for the fall of 1984 titled "Field reports--fall 1994". Plustek - flatbed